A história da ciência no contexto do ensino de ciências - Cararo, Lenoar Elói (2019)
The use of the History of Science as a tool in the teaching of Science can give meaning to the contents of Sciences and also provide the recognition that knowledge is the fruit of a social context and that is constantly built throughout the history of humanity. In this sense, in addition to knowing this trend of teaching Science, we seek to understand What is this, the History of Science for the teacher who teaches Science in the final years of elementary school? This research, besides a study on the legislation for the teaching of Sciences and the History of Science in the teaching of Sciences, using a qualitative research, based on phenomenology and hermeneutics, heard, through recorded testimonies, twenty four teachers from eleven state schools in the municipality of Francisco Beltrão, as well as questionnaires answered by eighty-one students, from five classes of 9th grade of Elementary School, Final Years, students from five different schools. From the teachers' statements, which were transcribed in full, we highlight the units of meaning from which emerged four open categories. These categories were described and interpreted in this work. Regarding the students 'answers, we tried to describe and interpret, even though the students' notes did not allow the construction of units of meaning and, consequently, of categories. In the light of the discussions around our research, some points were highlighted, that is, points that were more accentuated by the subjects of the research, such as the difficulties of daily school life, as much as the physical structure, from materials to human, as much as the passive posture of the student; criticism of teachers' initial and continuing training; the contextualization of science teaching and the use of experiments in science classes. As for our questioning, we understand, as explicit in the course of this dissertation, that many teachers do not use this tendency in the day to day classroom. The reasons given for not using this trend are, among others, the initial and continued formation of Science teachers, the teaching conception of teachers that give preference to other tendencies, as well as the lack of knowledge of the History of Science, by the research participants